SOURCES OF FINANCE OF MICRO AND SMALL ENTERPRISES IN BARAK VALLEY, ASSAM - Md. Iqbal Uddin Tapadar; Prof. Nikhil Bhusan Dey; Dr. Kingshuk Adhikari (International Journal of Management Studies (IJMS), 2021)
Micro and small enterprises not only generate employment but also utilise optimum resources, increase total production and exports and help in balanced regional development of the country. Finance is the life blood of the enterprise. The enterprise can fulfils its financial needs from long term sources of finance and short term sources of finance. Therefore, the present study has evaluated the sources of long-term finance of micro and small enterprises in Barak Valley. The study has also evaluated the sources of short-term finance of micro and small enterprises in the Valley. The enterprises which are registered with District Industries and Commerce Centers of the three districts of the Valley namely Cachar, Karimganj and Hailakandi districts as on 31-3-2012 and which are functioning have been studied in the present study. Sample size of the study is 246 of which 81.71 % are micro enterprises and 18.29 % are small enterprises. The study is based on the primary data. The sampling technique of the study is ‘convenience sampling’. The study found that the enterprises of the Valley generally use ‘own capital’ as their major source of both long term finance and short term finance.